Celebrating the contributions of Govindjee after his retirement: 1999–2020. Issue 4 (1st October 2020) - Stirbet, Alexandrina; Björn, Lars Olof; Shevela, Dmitry; Allakhverdiev, Suleyman I.; Nonomura, Arthur; Zhu, Xin-Guang; Lazár, Dušan; Pareek, Ashwani; Garab, Győző; Eaton-Rye, Julian J.
ABSTRACT: Govindjee, Professor Emeritus of Biochemistry, Biophysics and Plant Biology at the University of Illinois at Urbana-Champaign since 1999, is renowned for his pioneering work in the light reactions of photosynthesis and important accomplishments as educator, editor, historian and advocate of photosynthesis. In his honour, we review his contributions over the last twenty years, which were often achieved in collaboration with scientists working in laboratories around the world. We start with a short presentation about Govindjee's career and continue with a section highlighting his passion and dedication to teach the younger generations of students and researchers about photosynthesis. His research work is grouped under different areas, including primary photochemistry; the relationship of chlorophyll a fluorescence to photosynthesis; short time-scale regulation processes of photosynthesis; studies toward improving photosynthesis and biomass yields; and, mathematical modelling of photosynthesis and artificial photosynthesis. He is best known for the discovery of the key role of bicarbonate on the electron acceptor side of Photosystem II. We also present his active involvement in the recognition of scientists at conferences and beyond, as well as of those who are no longer with us. He is committed to keeping alive the pioneers and discoverers in the field of photosynthesis in the collective memory of those in the field.